Regulating cyclist law in Malaysia: a comparative study between Malaysia, United States Of America and Australia / Shafiq Mohd Sharif...[et al.] - Mohd Sharif, Shafiq; Anuar, Azza Aiisar; Azhari, Afiqah; Abdul Hamid, Mohd Najib Dzulnasreen (2013)
Bicycle, a vehicle or mode of transportation that exists way before any vehicles and had provide a concept and a catalyst towards the existence and creation of new technologies and had revolutionized the transportation industry. Transportation laws exists to regulate the conduct of road users and to protect other road users by providing some rights within the law. It was discovered that in some modern and well develop countries such as Australia and The United States of America had laws that governed the act of a cyclist and the operation of bicycles. Currently in Malaysia, there has been an increase in the usage of bicycle due to the campaign that has been made by state governments to promote green and healthy way of living. However there were lacunas in the laws enacted by the lawmakers to regulate the operation of bicycle. This study was conducted to identify and compare bicycling laws between other states such as Australia and The United States of America that had enacted laws to regulate the operation of bicycle. This study found out the authorities that are responsible to provide facilities for cyclist in each respective countries and several reforms that can be made towards the current available transportation laws in Malaysia to enable every state government to develop laws particularly on the operation of bicycle in order to protect cyclist rights and responsibilities in Malaysia.